ADHERENCE TO ANTIRETROVIRAL THERAPY FOR HIV/AIDS - Stela Maris de Mello Padoin; Samuel Spiegelberg Zuge; Érika Eberlline Pacheco dos Santos; Marcelo Ribeiro Primeira; Juliane Dias Aldrighi; Cristiane Cardoso de Paula (Universidade Federal do Paraná, 2013)
The study's objective was to determine the adherence to antiretroviral therapy in adults with the Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome, attended in a university hospital in the south of Brazil. This research has a quantitative approach, and is descriptive with a cross-sectional design, and was undertaken in 2011. The data was analyzed using the SPSS® program (version 17.0). The study population was 125 patients, in the age range of 20 to 49 years old; 44.0% were classified as non-adherent, of whom 29.3% stopped taking the medications because of use of alcohol or drugs; 26.2% due to the side effects; 17.6% for various reasons, and 4.5% because they were working. The need is emphasized to assess the behavior so as to undertake educational actions which allow the patients' cooperation for greater adherence to the treatment, reducing the morbidity and mortality of this health issue.